Global clinical trial landscape of stem cell-based therapies for osteoarthritis: trends and translational implications - Li, Xin; Zhao, Yue; Guo, Dongsheng; Yan, Chen; Zhang, Jian; Cheng, Lin; Dong, Yuefu (Frontiers in Cell and Developmental Biology, 2026)
ObjectiveOsteoarthritis (OA) is a leading cause of pain and disability worldwide, yet disease-modifying treatments remain limited. This study aimed to map the global registry landscape of interventional clinical trials of stem cell–based therapies for OA and summarize temporal, geographic, and design trends.MethodsWe conducted a systematic, registry-based landscape analysis of interventional clinical trials assessing stem cell therapies for osteoarthritis. Trial records were obtained from the Informa Pharmaprojects platform. Two researchers extracted and summarized trial characteristics, including year, phase, geographic distribution, target joint, cell source or type, autologous versus allogeneic strategy, administration route, outcome measures, and trial status. We then performed a descriptive trend analysis.ResultsWe identified a total of 224 eligible trials. The number of trials has steadily increased over time, with broad international participation. Most studies focused on knee osteoarthritis and used intra-articular administration. Mesenchymal stem cell-based products dominated, encompassing both autologous and allogeneic approaches, with growing attention to scalable allogeneic strategies. Primary endpoints were typically patient-reported pain and functional measures, while imaging and biomarker outcomes were often secondary. Published evidence syntheses suggest potential benefits in terms of pain and function, but conclusions are frequently limited by heterogeneity, risk of bias, and relatively short follow-up durations.ConclusionThe number of stem cell–based clinical trials for osteoarthritis is increasing globally, but heterogeneity in study designs and incomplete public reporting limit reliable conclusions about efficacy. Future research should prioritize standardizing products and protocols, employing more rigorous comparators and feasible blinding, extending follow-up periods, and ensuring transparent reporting to facilitate clinical translation.